TRANFORMASI PERADILAN PADA MASA UMAR BIN ABDUL AZIZ - asaari asaari (Lembaga Penelitian dan Pengabdian pada Masyarakat, Institut Agama Islam Negeri (IAIN) Kerinci, Jambi, 2017)
The renewal carried out by Umar bin Abdul Aziz in the judiciary is the Mazhalim court, whose object is the rulers, his family and himself. In this way the Mazhalim court initiated by Abdul Malik Bin Marwan has been very effective. Umar bin Abdul Aziz said